Arsitektur Keamanan Siber Dengan Protokol Denning-Sacco - Rama Dian Syah (Jurnal Informatika Universitas Pamulang, 2020)
Currently messages can be transmitted using information and communication technology. The message that is transmitted can contain data and information that is privacy or confidential. Messages that are confidential and privacy are only intended for parties that have been determined. Attacks by unauthorized parties may occur during the process of sending the message. Security in a private or confidential message exchange system is very much needed. The message exchange system is regulated by protocol to avoid certain party attacks. The method used in this research is the Denning-Sacco Protocol which is implemented in the exchange of messages from the sender to the recipient. This protocol uses a security key generated by the Key Distribution Center (KDC). The Denning-Sacco Protocol was developed from the Needham-Schroeder Protocol. This study produces an overview of the architecture of the Denning-Sacco Protocol to overcome the weaknesses of the Needham-Schroeder Protocol called the relpy attack. The steps of exchanging messages using the Denning-Sacco Protocol are explained in detail.